Bleomycin for orbital and peri-orbital veno-lymphatic malformations – A systematic review. Issue 2 (April 2021) - Faiz, Khunsa; Finitsis, Stephanos; Linton, Janice; Shankar, Jai Jai Shiva
Background: Orbital and peri-orbital venolymphatic malformations (VLM) are low flow vascular malformations. Intralesional bleomycin is now commonly being used to treat such malformations. Objective: The purpose of this systematic review is to synthesize evidence on the safety and efficacy of bleomycin/pingyangmycin sclerotherapy for the treatment of orbital and peri-orbital VLM. Methods: We searched Medline, Embase, Scopus and Cochrane database for studies reporting outcomes of bleomycin/pingyangmycin sclerotherapy for orbital and peri-orbital VLM between 1974 to April 5th, 2019. Nine retrospective cohort studies enrolling 132 patients were included. Two reviewers independently screened and extracted data and assessed the risk of bias. Predefined outcome measures were subjective and objective reduction of the lesion and associated complications. Results: Subjective reduction of the lesions was seen in 96.2% of the studies. Objective reduction of the lesion and symptomatic improvement were reported in 91.6 and 95% of the studies respectively. Non responders were 9.0%. Minor adverse events were reported in 18.1% of the studies. Major complications like pulmonary toxicity or pulmonary fibrosis was not encountered in any of the included studies. Quality of evidence was generally low. Conclusion: Bleomycin/pingyangmycin sclerotherapy is very effective and relatively safe for the treatment of orbital and periorbital VLM and is not associated with any major side effects including pulmonary fibrosis. Limitations: The systematic review is limited mainly due to low quality of the included studies with retrospective design.